The influence of depth of cut on cryogenic machining performance of hardened steel - KAYNAK, YUSUF (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2018)
This study provides an experimental study focusing on understanding the effectiveness of cryogenic cooling in cutting process of hardened steel under various cutting parameters. Liquid nitrogen and carbon dioxide are used in the machining performance experiments of hardened steel as cryogenic coolants. Turning process is carried out to test the role of cryogenic coolants for improving the machining performance of selected work material. A constant cutting speed and two different depth of cuts were selected as cutting parameters. To measure machining performance resultant forces and frictional condition, progression of tool wear, cutting temperature, and chip breakability, and surface quality of machined parts were considered and obtained results were also compared with the results obtained from dry machining. This study reveals that the effectiveness of cryogenic coolant to improve machining performance of this material also depends on the cutting parameters, namely depth of cut. While the effect of cryogenic coolants on cutting tool performance is limited at large depth of cut, cryogenic coolants show much better performance by showing obvious contribution for increasing tool life. Besides, it is observed that carbon dioxide substantially imcrease chip breakability.
Keywords: Cryogenic machining; machining performance; hardened steels; CUTTING FLUIDS; TOOL-WEAR; DRY